Responses of Cortical Extrastriate Area 21a Neurons Specialized in Motion Detection - Khachvankian, D.K.; Aslanian, H.R.; Harutiunian-Kozak, B.A.; Ghazaryan, A.L.; Kozak, J.A. (Нейрофизиология, 2015)
According to a generally accepted concept, the stationary structure of the receptive field of a visually sensitive central neuron predetermines transformation and central processing of the incoming information, including that related to moving visual stimuli. We found, however, that a small group of visually sensitive neurons of the cat extrastriate cortical area 21a does not fit this statement and exhibits no responses to stationary visual stimuli while responding vigorously to moving images. The results of our experiments showed that response patterns of these neurons to moving stimuli display high degrees of diversification and processing of incoming visual information. We suppose that these neurons may be strictly specialized in the detection and central processing of visual information necessary for perception of moving images.